Analysis of the expected error performance of cooperative wireless networks employing distributed space-time codes - Mietzner, J.; Thobaben, R.; Hoeher, P.A. (2004 IEEE Global Telecommunications Conference - Globecom, 2004)
In this paper, typical uplink scenarios in a cellular system are considered, where two cooperating mobile stations (serving, for example, as mobile relays) are transmitting the some information to a base station by using a distributed space-time coding scheme. Due to the distributed nature of the system, the transmitted signals are typically subject to different average path losses. For fixed distances between the mobile stations and the base station, the error performance of the distributed space-time coding scheme is determined analytically. Then, based on considerations concerning the spatial distribution of the mobile stations, analytical expressions for the distribution of the average path losses are derived and verified by means of simulations. These results are then used in order to compute the expected error performance of the system. It is shown that in most scenarios the average performance loss compared to a conventional multiple-antenna system with colocated antennas is less than 2 dB at a bit error rate of 10/sup -3/. The most significant performance losses occur for a large path-loss exponent.